IDENTIFIKASI RHODAMIN B PADA PRODUK KOSMETIK YANG BEREDAR SECARA ONLINE - Harpolia Cartika; Khairun Nida; Yetri Elisya (Jurnal Farmasi IKIFA, 2023)
The results of the routine supervision of the POM Agency, Red Dye K3 and Rhodamin B are often misused in cosmetic products. Rhodamine B is a textile dye that is quite harmful to the health of the human body, because it can cause irritation to the respiratory tract, damage to the liver, and cancer. This research aims to identify the presence of Rhodamin B in eyeshadow, lipstick, and blush circulating online, which using 5 samples for each products. The research method is an experimental method using Thin Layer Chromatography (TLC) to obtain hRf values ​​and calculate rhodamine B levels using UV-Vis Spectrophotometry 254 nm and 366 nm. The results showed that from the fifteen samples studied, 7 samples had an Rf value between 0.61-0.67 with a comparison standard Rf value of Rhodamine B of 0.62. The seven samples consisted of 1 sample of positive blush containing rhodamine B with value of 1.68%, 3 samples of positive eye shadow with values of 2.35%, 3.29%, and 3.26%, and 3 samples of positive lipstick with values of 1.17%, 1.22%, and 0.47%. This shows that 7 out of 15 cosmetic samples contain the harmful substance rhodamine B.